Genomics and the Contrasting Dynamics of Annual and Perennial Domestication. Issue 12 (December 2015) - Gaut, Brandon S.; Díez, Concepción M.; Morrell, Peter L.
Abstract : Plant domestication modifies a wild species genetically for human use. Among thousands of domesticated plants, a major distinction is the difference between annual and perennial life cycles. The domestication of perennials is expected to follow different processes than annuals, with distinct genetic outcomes. Here we examine domestication from a population genetics perspective, with a focus on three issues: genetic bottlenecks during domestication, introgression as a source of local adaptation, and genetic load. These three issues have been studied nominally in major annual crops but even less extensively in perennials. Here we highlight lessons from annual plants, motivations to study these issues in perennial plants, and new approaches that may lead to further progress. Trends: The study of a handful of annual crops has heavily influenced our understanding of the genetics of domestication. In contrast to annuals, the domestication of perennials has generally occurred more recently and involved clonal propagation. Annual and perennial domesticates appear to differ in the severity of domestication bottlenecks. New approaches to studying demographic history promise to yield fresh insights into these effects, particularly for perennials. Both annuals and perennials are understudied with respect to identifying the genetic basis of local adaptation and the contribution of introgression to modern cultigens. Recent studies suggest that wild-to-crop introgression has been a particularly important feature of the evolution of perennial crops. The 'cost of domestication', in terms of increased genetic load, is an area of growing interest. The magnitude and effect of genetic load remains uncharacterized for perennial plants, where an important contributor to load may be somatic mutations among clonal variants.